Gastric Ulcers in Alpacas— Clinical, Laboratory, and Pathological Findings - Neubert, Saskia; Puff, Christina; Kleinschmidt, Sven; Kammeyer, Patricia; von Altrock, Alexandra; Wendt, Michael; Wagener, Matthias Gerhard (Frontiers in Veterinary Science, 2022)
Gastric ulcers are a common finding in post-mortem examinations of South American camelids (SAC), but diagnosis in living animals is often difficult. The aim of this study was to provide an overview of the incidence of gastric ulcers in alpacas, common concomitant diseases, and clinical as well as laboratory findings to facilitate diagnosis for veterinarians. For this purpose, a total of 187 necropsy reports of alpacas were evaluated, including clinical and laboratory findings on the living animal. A total of 23.5% of the animals (n = 44) were found to have gastric ulcers, nine were perforated. Compartment 3 was most frequently affected by gastric ulcers. No sex predilection could be detected, but animals one year of age and older were more frequently affected by gastric ulcers than animals under one year of age. Alpacas with gastric ulcers were presented to the clinic due to different non-specific symptoms. In alpacas with gastric ulcers, significantly more organs or organ systems besides the stomach revealed clinical findings than in animals without gastric ulcers. Of the 44 animals with gastric ulcers, a total of 21 alpacas (47.7%) had a poor nutritional status, but cachexia was not significantly more frequent in animals with gastric ulcers than in other dissected animals without ulcers. Hematologic investigations revealed a significantly lower white blood count and significantly lower segmented neutrophils than in deceased animals without ulcers. Compared to animals discharged after treatment, alpacas that died with gastric ulcers had significantly higher levels of band neutrophils and fewer eosinophils and basophils. Occult blood in feces was found in three of 12 animals with gastric ulcers examined for occult blood. In summary, gastric ulcers are a common problem in SAC, which is difficult to diagnose clinically or by laboratory investigations. As these are often chronic processes involving other organ systems, regular monitoring of the animals´ nutritional status and early detection of disease symptoms may help to prevent gastric ulcers.